Examining the influence of family physician supply on district health system performance in South Africa: An ecological analysis of key health indicators - Klaus B. von Pressentin; Bob J. Mash; Tonya M. Esterhuizen (AOSIS, 2017)
Background: The supply of appropriate health workers is a key building block in the World Health Organization's model of effective health systems. Primary care teams are stronger if they contain doctors with postgraduate training in family medicine. The contribution of such family physicians to the performance of primary care systems has not been evaluated in the African context. Family physicians with postgraduate training entered the South African district health system (DHS) from 2011. Aim: This study aimed to evaluate the impact of family physicians within the DHS of South Africa. The objectives were to evaluate the impact of an increase in family physician supply in each district (number per 10 000 population) on key health indicators. Setting: All 52 South African health districts were included as units of analysis. Methods: An ecological study evaluated the correlations between the supply of family physicians and routinely collected data on district performance for two time periods: 2010/2011 and 2014/2015. Results: Five years after the introduction of the new generation of family physicians, this study showed no demonstrable correlation between family physician supply and improved health indicators from the macro-perspective of the district. Conclusion: The lack of a measurable impact at the level of the district is most likely because of the very low supply of family physicians in the public sector. Studies which evaluate impact closer to the family physician's circle of control may be better positioned to demonstrate a measurable impact in the short term.